Extracorporeal life support allows lung transplant in anti-MDA5+ rapidly progressive interstitial lung disease. Issue 5 (26th May 2022) - Bay, Pierre; Pineton de Chambrun, Marc; Roux, Antoine; Bunel, Vincent; Combes, Alain; Israël-Biet, Dominique; Zuber, Benjamin; Nunes, Hilario; Allenbach, Yves; Uzunhan, Yurdagül
Anti-melanoma differentiation-associated gene 5 antibody (anti-MDA5) dermatomyositis (DM) is a rare subtype of idiopathic inflammatory myopathy, associated with severe interstitial lung disease (ILD) [1]. A subset of anti-MDA5 DM patients with rapidly progressive ILD (RP-ILD) have a very poor prognosis, with reported mortality rates reaching 80–84% [1, 2]. In this clinical setting, the use of extracorporeal life support (ECLS) is questionable, as reported in several studies that emphasise the futility of a bridge-to-recovery strategy [2, 3]. In this respect, emergency lung transplantation of previously unlisted patients on ECLS is under debate [4–6]. Yet, new therapeutic regimens, especially the early association of calcineurin inhibitors and cyclophosphamide [7], Janus-kinase inhibitors (JAKi) [8] or plasma exchange [9], have been recently associated with better outcomes of anti-MDA5 DM, fuelling hopes for a successful treatment of RP-ILD patients. Data on the outcome of anti-MDA5 RP-ILD requiring ECLS in the modern era are therefore urgently awaited. Anti-MDA5 RP-ILD has a poor prognosis and a high mortality rate. This study found that emergency lung transplantation in anti-MDA5 RP-ILD patients requiring ECLS has a favourable disease outcome, irrespective of prior treatment regimen. https://bit.ly/3gHKPt6